The location, strength, and mechanisms behind marine biogeographic boundaries of the east coast of North America. Issue 7 (18th November 2014) - Pappalardo, Paula; Pringle, James M.; Wares, John P.; Byers, James E.
<x xml:space="preserve">Abstract</x> Classic biogeographic studies emphasized differences in species composition between regions to define biogeographic provinces and delimit biogeographic boundaries. Here we analyze the permeability of biogeographic boundaries to different species to gain mechanistic insight into the processes that maintain species boundaries in the coastal ocean. We identify sites with high frequencies of range boundaries using almost 1800 benthic marine invertebrates along the northwestern Atlantic coast and address whether their magnitude and location vary as a function of species' taxonomy, pelagic larval duration and depth distribution. We observed clusters of species boundaries at Cape Hatteras, Cape Cod and the Bay of Fundy that are largely independent of taxonomic group. However, the boundaries were permeable and asymmetric, with a higher percentage of species shared across boundaries in the equatorward direction (82%) than in the reverse direction (59%). This pattern was particularly strong for shallow species (median occurrence depth < 20 m). Pelagic larval duration was more important to explain distributions of boundaries for deep species (median occurrence depth > 20 m), where species with long larval dispersal had significantly higher occurrence of boundaries than species with short larval dispersal. When they do exist, species boundaries seem to be set by the interaction of currents, depth distribution and pelagic larval duration. Importantly, species boundaries tend to be pinned to regions of reduced water transport, which might explain why species boundaries are concentrated in narrow geographical areas.